Further investigation of the impact of foveal and parafoveal word frequency on parafoveal preview during Chinese reading - Yue Sun; Sainan Li; Yancui Zhang; Jingxin Wang (PLoS ONE, 2026)
Parafoveal preview is crucial for cognitive language processing, significantly improving reading efficiency. However, the factors influencing this process remain ambiguous. Given the unique characteristics of Chinese, it is unclear whether the processing load of foveal words, parafoveal words, or a combination of both impacts parafoveal preview. To investigate these issues, we employed eye-tracking technology and manipulated the frequency of both foveal and parafoveal words, as well as two types of preview. Sixty-four valid participants participated in the study, with two-character words serving as foveal and parafoveal stimuli. The results indicated that the frequency of foveal words affected the preview benefit: as the foveal load increased, the preview benefit decreased, demonstrating the foveal load effect. However, parafoveal word frequency had no effect on the preview benefit, nor was there any interaction between foveal and parafoveal word frequency in influencing the preview benefit. Additionally, both foveal and parafoveal processing loads independently affected the forward saccade length: lower foveal processing load resulted in longer forward saccades, while greater parafoveal preview availability also increased saccade length. These findings support the Chinese Reading Model (CRM) and provide valuable empirical evidence for refinement.